Improving the Quality and Efficiency of Product Marketing at Luh Buleleng MSMEs - I Wayan Ardiyasa; Ni Made Ayu Juli Astari; Ni Luh Putu Unix Sumartini; Devi novayanti, Putu; Luh Putu Maitri Maha Dewi; Anak Agung Istri Agung Ambuja Savitri (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
Processed foods without preservatives, artificial sweeteners, and MSG are increasingly in demand as they are considered healthier and more natural. Therefore, Micro, Small and Medium Enterprises (MSMEs) in the healthy food sector have great potential to improve the Indonesian economy. Luh Buleleng, an MSME owned by Ms. Luh Wiriadi from Banjar Dinar Pasar, Anturan Village, Buleleng District, produces healthy food such as banana, taro, and breadfruit chips without MSG, artificial sweeteners, and preservatives. However, Luh Buleleng faces problems such as limited production equipment and simple packaging, and has not utilized digital marketing. The solutions offered include the addition of production equipment, redesigning product packaging, and training in the use of e-commerce applications such as Tokopedia and Shopee to expand marketing. The results of this service are in the form of additional production equipment so as to help partners increase production, redesign product packaging to make product packaging more attractive and partners begin to apply digital marketing through E-commerce applications, namely Tokopedia and Shopee so as to expand marketing reach and increase product sales